Nonlinear on-line Estimation and Adaptive Control of a Wastewater Treatment Bioprocess - Roman, M.; Selişteanu, D. (Elektronika ir Elektrotechnika, 2012)
This work approaches the on-line estimation and adaptive control of a wastewater treatment process, which takes place inside a bioreactor. This bioprocess is highly nonlinear, the available state measurements are lack and moreover the reaction kinetics is not perfectly known. The kinetic parameters are estimated by using high-gain nonlinear observers and the unavailable states are reconstructed by using an asymptotic state observer. The control goal is to keep a low level of pollutant concentration. An adaptive control law is designed by combining a linearizing controller with the nonlinear observers. Numerical simulations are included to test the performances of the proposed algorithms. Ill. 8, bibl. 17 (in English; abstracts in English and Lithuanian). DOI: http://dx.doi.org/10.5755/j01.eee.117.1.1047